DINAMIKA KOMUNIKASI POLITIK DALAM PILKADA DI INDONESIA - Samsul Rani (Alhadharah: Jurnal Ilmu Dakwah, 2019)
The phenomenon of 2018 regional elections can be seen in the selection of candidate pairs, party coalitions, and the delivery of political messages conveyed by political parties and candidate pairs, which have given birth to a variety of maneuvers, rivalries in the formulation of political strategies to support or subdue each other. This communication constellation has shaped the dynamics of Pilkada political communication in Indonesia. Of the 171 regions that held elections, 16 of them had a single candidate whose average candidate pair was supported by 6 to 12 political parties. The phenomenon of mutually changing pairs of candidates or revoking support has become a public concern in the elections. This can be caused by unfulfilled supporting requirements, lobbying from other parties, low electability, legal cases, and political dowry. The role of the mass media in Pilkada is very good, because the mass media has become an independent and transparent party, the news related to the Pilkada is published based on facts and data, it does not appear that mass media "fry" the issues so that the condition of the community is more conducive and the elections run safely.